2017
DOI: 10.1016/j.socscimed.2017.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Social support, flexible resources, and health care navigation

Abstract: Recent research has focused attention on the role of patients’ and clinicians’ cultural skills and values in generating inequalities in health care experiences. Yet, examination of how social structural factors shape people’s abilities to build, refine, and leverage strategies for navigating the health care system have received less attention. In this paper I place focus on one such social structural factor, social support, and examine how social support operates as a flexible resource that helps people naviga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 36 publications
(56 reference statements)
1
54
0
Order By: Relevance
“…Children's disease symptoms in single-parent homes may be given greater attention due to the increased level of affection or overprotection received from their single parent. Children in single-parent households would also use more social resources, such as after school care, due to their parent's work conditions, [30] which may also result in an increased detection likelihood of any disease symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Children's disease symptoms in single-parent homes may be given greater attention due to the increased level of affection or overprotection received from their single parent. Children in single-parent households would also use more social resources, such as after school care, due to their parent's work conditions, [30] which may also result in an increased detection likelihood of any disease symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…A pediatric cancer diagnosis requires parents to manage their child’s complicated treatment protocol, including regular clinic visits and hospital stays, all while simultaneously fulfilling other obligations related to work and family. 24 Due to the intensive demands of caregiving, pediatric cancer parents may find themselves physically removed from traditional sources of social support (friends and family), making online platforms a potential tool for busy parents to seek information and support. 11 While previous research has vastly expanded the understanding of the content and engagement with cancer-related information on SNS, few studies have examined when and why caregivers turn to social media for cancer-related information and how users appraise the credibility of cancer-related information obtained on SNS.…”
Section: Introductionmentioning
confidence: 99%
“…According to a study conducted by E. A. Gage-Bouchard (2017), most parents who received aids through their personal social networks were most comfortable in balancing their competing demands. This enabled them to effectively comply with their agencies' hopes of parents' proper participation in child care (Gage-Bouchard, 2017). In this way, social support provided some families with exible resources, which enabled them to acclimatized to the needs of caring for children with cancer more quickly.…”
Section: Resultsmentioning
confidence: 99%
“…In this way, social support provided some families with exible resources, which enabled them to acclimatized to the needs of caring for children with cancer more quickly. It also raised a fruitful social relationship between parents and their medical care providers which played an active impact in the health of their children (Gage-Bouchard, 2017). Notably, quite a number of studies on social support and health have shown that emotional, logistical, information and nancial support from personal networks enhance people's coping choices in managing serious diseases (K. P. Smith & Christakis, 2008;Thoits, 2011).…”
Section: Resultsmentioning
confidence: 99%